Implementation of the Istanbul Convention into the National Criminal Legislation in Poland - Hypś, Sławomir (Review of European and Comparative Law, 2023)
The Council of Europe Convention on preventing and combatting violence against women and domestic violence (further: Istanbul Convention) became part of the Polish legal system on August 1, 2015. The ratification process of the Istanbul Convention was marked with difficulties from its very opening for signature. The provisions of the Convention have caused – and continue to arouse – a range of extreme emotions and doubts. The fierce dispute that has emerged over the implementation of the Convention in Poland at some point even led to action being taken for termination. As things have been to date, Poland has not terminated of the Istanbul Convention. Five years following ratification of the Convention, in March 2020, Poland submitted a report on the implementation of measures giving effect to its provisions into the Polish legal system, as required under the monitoring mechanism. Poland’s report was considered by GREVIO, with an assessment made of Polish legislation in this regard and an evaluation report issued in June 2021. Notwithstanding the comments that Poland made to the GREVIO report, the key conclusions of the assessment should be highlighted as regards compliance of Polish criminal legislation with the standard of protection of women against violence, including domestic violence, under the Convention. Since the Convention was opened for signature, and in particular since its ratification, the Polish legislator has introduced a range of amendments to the Criminal Code aimed at raising the standard of protection for victims of domestic violence and of effective prosecution of offenders. This text highlights the most important of these changes and presents the current state of implementation of the Istanbul Convention into Polish criminal law.